MOSSBAUER SPECTRAL STUDIES OF TRI-DI- AND CHLORODI-ORGANOTIN CARBOXYLATES (Biological Sciences - PJSIR, 2001)
119mSnMossbauer data are reported for some organotin derivatives of type R3SnL, R2SnCIL, R2SnL2 and [(~SnL)20l2 where R = CH3, C2Hs ' n-C4H9, C6Hs ' Clll!, C6I-\CH2 and L= trans-3-(2-furanyl)-2-propenoic (FA) and trans-3-(3- methylphenyl)-2-propenoic (CA) acids. The stereochemistry of these derivatives and C-Sn-C bond angles for R2SnL2 and [R2SnL)20l2 are calculated.